Descriptions of three new species of Philodinida (Rotifera, Bdelloidea) from Korea - Song, Min Ok; Lee, Chang-Ho (Zootaxa, 2024)
A taxonomic study on bdelloid rotifers collected from terrestrial habitats such as mosses and leaf litter at two different locations in Korea resulted in three new species, Habrotrocha changhoi n. sp., H. microcornis n. sp. and Philodina undulata n. sp. Habrotrocha changhoi n. sp. is easily distinguished from its congeners by five small dorsal humps on preanal pseudosegment. The most significant diagnostic characteristic of Habrotrocha microcornis n. sp. is the tiny spurs with very wide interspace, which is about 4–5 times as wide as spur base width. Habrotrocha changhoi n. sp. and H. microcornis n. sp. are the first new Habrotrocha species from Korea. The most prominent characteristics that distinguish Philodina undulata n. sp. from its congeners are the first trunk pseudosegment expanded anteriorly in feeding as well as the plump trunk that has wavy lateral margins and abruptly tapers to rump in feeding. Here these three new species are described in detail and illustrated. In addition, the partial sequences of mitochondrial cytochrome c oxidase subunit I gene (CO1) for these three new species are provided here.